The earnings-price anomaly - Ball, Ray (Journal of Accounting and Economics, 1992)
This review explores systematic explanations for the anomalous evidence in the relation between accounting earnings and stock prices. The anomaly is that estimated future abnormal returns are predicted by public information about future earnings, contained in (1) current earnings and (2) current financial statement ratios. The current-earnings anomaly appears due to either market inefficiency or substantial costs of investors acquiring and processing information, the choice depending on one's priors concerning these costs and one's definition of market ‘efficiency’. The financial-statement-information anomaly appears due to accounting ratios proxying for stocks' expected returns. Anomaly seems likely to be a permanent state.